Distribution characteristics, source identification, and health risk assessment of heavy metals in surface water and groundwater: a case study in mining-affected areas - Wang, Jiangyulong; Zhang, He; Liu, Junjian; Hu, Suduan; Shi, Jingtao; Li, Xia; Song, Dongyang; Niu, Xueyao (Frontiers in Water, 2025)
Heavy metals pose a significant threat to the water environment and human health. However, mining activities play a critical role in releasing various heavy metals into the environment. The present study aimed to evaluate the distribution characteristics, source identification, and health risk assessment of heavy metals in surface water and groundwater of Pingquan City (Hebei, China), which is a typical industrial city. Nineteen water quality indicators include pH, strontium (Sr), arsenic (As), lithium (Li), zinc (Zn), barium (Ba), lead (Pb), aluminum (Al), copper (Cu), manganese (Mn), nickel (Ni), cadmium (Cd), chromium (Cr), ferrum (Fe), cobalt (Co), selenium (Se), argentum (Ag), vanadium (V), and molybdenum (Mo), were selected; a total of 336 water samples from monitoring sites in Pingquan City were monitored, and the water quality was assessed; then the human health risks that residents possibly faced through ingestion and dermal pathways were assessed. The results showed that surface water in the Bao River Basin exhibited higher concentrations of Fe (107.71 μg/L) and As (1.37 μg/L) compared to those in other river basins. In contrast, groundwater in the Bao River Basin had significantly higher concentrations of Fe and Mn than those in other river basins, reaching 149.62 μg/L and 53.45 μg/L, respectively. According to the Water Quality Index (WQI) results, each river basin exhibits a WQI value below 50. Additionally, from a health risk assessment perspective, As in the study area does not pose health hazards that exceed acceptable risk levels in most exposure scenarios.